Integration of Renewable Generation and Elastic Loads into Distribution Grids - Ardakanian, Omid.; Keshav, S.; Rosenberg, Catherine; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This brief examines the challenges of integrating distributed energy resources and high-power elastic loads into low-voltage distribution grids, as well as the potential for pervasive measurement. It explores the control needed to address these challenges and achieve various system-level and user-level objectives. A mathematical framework is presented for the joint control of active end-nodes at scale, and extensive numerical simulations demonstrate that proper control of active end-nodes can significantly enhance reliable and economical operation of the power grid.
Introduction -- Related Work -- System Model -- Optimal Control of Active End-nodes -- Evaluation -- Conclusion.
Keywords: Telecommunication; Computer networks .; Communications Engineering, Networks; Computer Communication Networks